2012
DOI: 10.2981/09-099
|View full text |Cite
|
Sign up to set email alerts
|

Hunting influences the diel patterns in habitat selection by northern pintails Anas acuta

Abstract: Northern pintail Anas acuta (hereafter pintail) populations wintering within Suisun Marsh, a large estuarine managed wetland near San Francisco Bay, California, USA, have declined markedly over the last four decades. The reasons for this decline are unclear. Information on how hunting and other factors influence the selection of vegetation types and sanctuaries would be beneficial to manage pintail populations in Suisun Marsh. During 1991-1993, we radio-marked and relocated female pintails (individuals: N ¼ 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
(61 reference statements)
4
33
0
Order By: Relevance
“…During migration, several thousand L. limosa (< www.rspb.org.uk/ birds-and-wildlife/wildlife-guides/bird-a-z/black-tailedgodwit >) travel across the United Kingdom passing through suitable habitats for the buttonweed (Wernham et al 2002, Alves et al 2010, < www.brc.ac.uk/plantatlas/ >). However, this bird may not be the most important avian vector for C. coronopifolia, since seeds are eaten by ducks in Australia and North America (Raulings et al 2011, Casazza et al 2012. van Der Toorn (1980) also suggested that greylag geese Anser anser may have a role in its spread in northern Europe.…”
Section: Buttonweed An Alien Spread By Waterbirds?mentioning
confidence: 99%
“…During migration, several thousand L. limosa (< www.rspb.org.uk/ birds-and-wildlife/wildlife-guides/bird-a-z/black-tailedgodwit >) travel across the United Kingdom passing through suitable habitats for the buttonweed (Wernham et al 2002, Alves et al 2010, < www.brc.ac.uk/plantatlas/ >). However, this bird may not be the most important avian vector for C. coronopifolia, since seeds are eaten by ducks in Australia and North America (Raulings et al 2011, Casazza et al 2012. van Der Toorn (1980) also suggested that greylag geese Anser anser may have a role in its spread in northern Europe.…”
Section: Buttonweed An Alien Spread By Waterbirds?mentioning
confidence: 99%
“…Our study provided data only on overall daytime habitat use patterns but may have obscured consistent diel variation in use patterns for birds such as cranes, which may use different cover types for morning and afternoon foraging periods than for midday loafing (Ivey 2015), and for waterfowl and shorebirds, which may vary by species, daily environmental conditions, and season in the degree to which they forage in the day or night (Miller et al 1985;McNeil et al 1992;Austin et al 2016). Similarly, our data do not account for any differences in habitat use by ducks between day and night in response to disturbance from hunting (Casazza et al 2012;Coates et al 2012). Also, the probability of detection for some birds in tall or dense cover types (e.g., rice in growing season) may be less than 1, possibly resulting in lower estimated densities.…”
Section: March 2019mentioning
confidence: 62%
“…Otherwise, hunting is not permitted in these areas. Restrictions on hunting activity may have positively influenced mottled duck use of Stormwater Treatment Areas during the hunting season because other duck species also have been found to increase their use of non‐hunted sanctuaries during the hunting season (Cox and Afton , Evans and Day , Casazza et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Restrictions on hunting activity may have positively influenced mottled duck use of Stormwater Treatment Areas during the hunting season because other duck species also have been found to increase their use of non-hunted sanctuaries during the hunting season (Cox and Afton 1997, Evans and Day 2002, Casazza et al 2012. Many rural females left Stormwater Treatment Areas and moved to agricultural habitats at the start of the breeding season.…”
Section: Discussionmentioning
confidence: 99%